1994
DOI: 10.1091/mbc.5.2.135
|View full text |Cite
|
Sign up to set email alerts
|

cdc25 is one of the MPM-2 antigens involved in the activation of maturation-promoting factor.

Abstract: MPM-2 antigens, a discrete set of phosphoproteins that contain similar phosphoepitopes recognized by the monoclonal antibody MPM-2, are phosphorylated during M-phase induction. Our previous studies suggested that certain MPM-2 antigens are involved in the appearance of maturation-promoting factor (MPF) activity. Because the central mitotic regulator cdc2 kinase has been shown to exhibit MPF activity, we explored the possibility that certain MPM-2 antigens are regulators of cdc2 kinase. We found that MPM-2 bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
63
1

Year Published

1995
1995
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(65 citation statements)
references
References 51 publications
1
63
1
Order By: Relevance
“…In the interphase-arrested extracts, H1 kinase activity remained low, the tyrosine-phosphorylated form of Cdc2 accumulated, cyclin B2 remained hypophosphorylated, Cdc25C did not undergo hyperphosphorylation, and nuclei continued to enlarge. In addition, M-phasespecific phosphoproteins were not detected with the MPM-2 antibody (Davis et al, 1989;Kuang et al, 1994;our unpublished results), providing further support that these extracts remained in interphase. The interphase arrest persisted for at least 130 min, even though control extracts had completed at least two cell cycles by this time.…”
Section: Discussion P42mapk Activation Inhibits Entry Into M-phase Inmentioning
confidence: 82%
“…In the interphase-arrested extracts, H1 kinase activity remained low, the tyrosine-phosphorylated form of Cdc2 accumulated, cyclin B2 remained hypophosphorylated, Cdc25C did not undergo hyperphosphorylation, and nuclei continued to enlarge. In addition, M-phasespecific phosphoproteins were not detected with the MPM-2 antibody (Davis et al, 1989;Kuang et al, 1994;our unpublished results), providing further support that these extracts remained in interphase. The interphase arrest persisted for at least 130 min, even though control extracts had completed at least two cell cycles by this time.…”
Section: Discussion P42mapk Activation Inhibits Entry Into M-phase Inmentioning
confidence: 82%
“…Two M-phase regulators of cdc2, the wee-1 tyrosine kinase and the cdc25 phosphatase (for review, see Coleman and Dunphy, 1994) are now proven MPM-2 phosphoproteins (Kuang et al, 1994;Mueller et al, 1995). It is reasonable to speculate that these proteins are candidate MPM-2 antigens in NFTcontaining neurons as well.…”
Section: Discussionmentioning
confidence: 99%
“…Mitotic entry is accompanied by the phosphorylation of several molecules, including mitotic protein monoclonal 2 (MPM-2), that may regulate the mitotic processes. 24,25 Immunostaining using antiphospho-Ser/Thr-Pro and MPM-2 antibody (05-368; EMD Millipore, Bedford, MA) showed that the number of cells at M phase was increased in WTmice 1 day after IRI compared with in KO mice, but it only accounted for a small fraction of the cells arrested at G2/M phase, indicating that most p-H3-positive cells were arrested at G2 phase (Supplemental Figure 4, B and C). Figure 6A).…”
Section: Loss Of P53 Reduced Cell Cycle Arrest After Irimentioning
confidence: 99%